Defining and Categorizing Nonpharmacologic Interventions in the Older Population: A Systematic Review - Kooijmans, Eline C M; Hoogendijk, Emiel O; Drapała, Natalia; Antonenko, Olena; Burchell, George L; Barańska, Ilona; Pokladníková, Jitka; Szczerbińska, Katarzyna; Fialová, Daniela; van Hout, Hein P J; Joling, Karlijn J (Journal of the American Medical Directors Association, 2025)
OBJECTIVES: Nonpharmacologic interventions (NPIs) constitute an important part of treatment for older adults, cover a broad and diverse range of interventions, and have advantages over pharmacologic interventions (eg, limited adverse side effects). However, an unambiguous definition of NPIs is still lacking. Defining NPIs may facilitate research on this topic and enhance comparability of results between studies, and might help to face the challenges of recognition, acceptation, funding, and implementation. Therefore, the aim of this review was to provide an overview and comparison of the definitions of NPIs used in the current literature on older adults. DESIGN: A systematic review was performed to provide an overview of the definitions of NPIs that are used in the current literature on older populations and to organize the characteristics involved in the definitions. SETTING AND PARTICIPANTS: People ≥60 years of age were included, not limited to a specific setting. METHODS: A systematic search was performed in the following 5 databases: PubMed, Embase, Clarivate Analytics/Web of Science Core Collection, Cumulative Index to Nursing and Allied Health Literature, and Wiley/Cochrane Library. The time frame within the databases was from inception to December 4, 2023. Review articles, editorials and consensus papers were included. RESULTS: We included 28 articles. We organized the definitions of NPI according to 4 different aspects: types of interventions involved, target population, goals the interventions addressed, and requirements of the interventions. Definitions in the current literature can generally be divided into 2 groups: NPIs described as not involving medication, and more elaborated multidomain definitions. Based on the results, we formulated criteria for types of interventions that can be considered an NPI. CONCLUSIONS AND IMPLICATIONS: Using current descriptions and characteristics, elements for a new definition for NPIs were proposed. To improve research in this field, consensus needs to be reached regarding elements covered by a definition of NPIs.
Keywords: Aged, 80 and over; nondrug interventions; care for older persons; Male; senioři nad 80 let; nonpharmacologic interventions; Aged; lidé; Female; mužské pohlaví; ženské pohlaví; senioři; lidé středního věku; Therapeutics; Humans; terapie; Older people; Middle Aged